Of Internet born: idolatry, the Slender Man meme, and the feminization of digital spaces. Issue 2 (4th March 2018) - Maddox, Jessica
Abstract: This paper examines 96 US and British Commonwealth articles on the 2014 Wisconsin Slender Man stabbing. Using critical textual analysis, this study examined how media took a horror-themed meme from the underbelly of the Internet and curated a moral panic, once the meme was thrust into the international limelight. Because memes are a particular intersection of images and technology, media made sense of this meme-inspired attack in three ways: (1) through an idolatrous tone that played on long-standing Western anxieties over images; (2) by hyper-sensationalizing women's so-called frivolous uses of technology; and (3) by removing blame from the assailants and, in turn, finding the Internet and the Slender Man meme guilty in the court of public opinion. Through this tripartite rhetoric, this study suggests that when media set out to curate a moral panic surrounding images and technology, together, the discourse that emerges is one that feminizes the Internet, turning it into technology-as-mother and image-as-child. This study also suggests this is the case because when women receive macro-level structure equality, micro-level inequities and attempts of control against them increase. Digital and image rhetoric are not exceptions.